Atenção conjunta em sala de aula no ensino remoto: a emergência de gestos híbridos nas interações com criança surda - Sena, Fábia Sousa de (2021)
This research aims to analise the multimodal elements that sustains the scenes of Joint Attention in the context of two distincts linguistics sistems (Libras and Portuguese Language), in the emergency remote teaching period (ERP) considering that, because of the Covid-19 pandemic, the classes took a new shape, thus, the research was made through technological resources. The perspective of the presente research is the multimodality of language, in which gesture and speech are part of the same cognitive and signicant matrix (McNeill, 2003). For the construction o four theoretical framework we are guided by scholars of the line of research in language acquisition that presente in their proposals the importance of social interactions for the development of human language. Thus, in relation to gestures and Joint Attention we refer to the studies of Cavalcante (1994; 2012; 2015; 2021); Tomasello (1995; 2003); Costa Filho (2011; 2015) and Goldin-Meadow (1979; 2005). Regarding multimodality, we take as our theoretical approach McNeill (1985; 2003; 2006); Kendon (1982; 2009); Cavalcante (2009; 2010; 2015); and Ávila-Nóbrega (2010; 2015; 2017). About the use of virtual tools in the classroom we refer to Matos (2020) and Rojo (2012). Furthermore, in relation to research on deafness, we entered the studies of Quadros (2004); Lacerda e Lodi (2006); and Adriano (2010). The methodology was conducted based on the theoretical and methodological assumptuions of quantitative research of interpretativist nature and, as a tool for achieving the proposed objectives, we used a field research for data generators, which occurred in a school of João Pessoa-PB. Participated in the research two deaf children, a regular classroom teacher of the 3rd year of the Early Years Elementary School; and two Libras interpreters. We conducted remote classroom observations that took place via FVNexA Google Meet in the months of April, May, June and July of the current year. The data collected were transcribed and analyzed in ELAN software, which enable the accuracy in the results that were found about the multimodal elements that sustain the scenes of Joint Attention during communicative ineractions performed in the remote context with deaf children and/or teacher/Libras interpreters. The results obtained point to the direction of the gaze as the element of higher occurence, highlighting the relevance of this elemento for the realization of interaction because of the visual linguistic condition of the deaf subject; the need of using hybrid gesture in these interactions, since deaf children do not have the mastery of sign language and communicative partners use the oral language, in this contexts, gestures emerge that circulate in both systems, thus, we emphasize the recurrence of the gesture of pointing; Finally, we highlight the Joint Attention as na importante strategy developed by the interpreters and/or teacher for the establishment of interaction with deaf children. Thus, we highlight the essential use of multimodal elements for the establishment of scenes of Joint Attention in interactive situations during the transitional period of deaf children.